PRINCIPLES OF EDUCATIONAL PROGRAMS FORMATION IN IT SPHERE - Yuliya Rizen Yuliya S. Rizen; Alena A. Zakharova; Mikhail G. Minin (Высшее образование в России)
Abstract. The sphere of information technology is the most rapidly evolving and has a number of features that do not allow students to study all existing technologies, development environments, etc. In this connection, the paper analyzes the global trends in the evolution of IT sphere, determines the features of Russian trends. Basing on the comparative analysis of professional education all over the world the authors propose the model of IT-sphere organization. This model allows forecasting further growth of the IT industry, identifying promising areas of education and their content, necessary for educational programs design.